Regional-specific algorithmic stand density management diagram for black spruce - Newton, P.F (Northern journal of applied forestry, 1998)
A regional-specific algorithmic stand density management diagram was developed for managed upland black spruce (Picea mariana [Mill.] B.S.P.) stands applicable to Newfoundland, New Brunswick, Quebec, and Ontario. Specifically, the IBM-compatible PC-based algorithm (1) graphically illustrates site-specific size-density trajectories for 8 user-specified initial density regimes, (2) calculates and subsequently tabulates periodic yield estimates from 5-50 yr by 5 yr intervals for mean dominant height, density, mean volume, total volume, total merchantable volume, quadratic mean diameter, and basal area, (3) given (2), graphically illustrates empirically derived yield production curves for total merchantable volume per hectare and number of stems per cubic meter with user-specified operability criteria superimposed, and (4) given (3), calculates and subsequently tabulates the minimum time required to attain operability status. The utility of the algorithm is demonstrated within the context of determining site-specific initial densities required to attain user-specified operability criteria. Procedures for acquiring the executable version via the Internet are also included.